On the cusp of the canon English children’s literature in the first half of the 19th century - Williams, Sandra (2020)
This period, the first half of the 19th century, stands on the cusp of the first Golden Age of English children’s literature. While publications from the mid-1800s onwards, such as Alice’s Adventures in Wonderland, The Secret Garden and The Wind in the Willows, have become part of the cultural landscape, those from the first half of the 19th century are largely unfamiliar and forgotten. If read at all, they are studied by academics rather than read by children. Publications at that time reveal the tensions between the perceived need for improving, moralising books and those that might give pleasure to the reader. It will be argued in this article that amongst the more didactic works, there are indicators of what was to follow. Attention is drawn to chapbooks for children and to a number of titles which have enjoyed a degree of longevity.
Razdoblje prve polovice devetnaestoga stoljeća stoji na samom rubu prvoga „zlatnoga doba“ engleske dječje književnosti. Dok su djela objavljena od sredine toga stoljeća nadalje, poput romana Aličine pustolovine u Čudozemskoj, Tajni vrt i Vjetar u vrbama, postala dio kulturnoga krajobraza, ona iz prve polovice devetnaestoga stoljeća uglavnom su nepoznata i zaboravljena. Ako ih se i čita, čitaju ih znanstvenici i stručnjaci radi akademskoga istraživanja, a ne djeca. Naslovi objavljeni u to vrijeme otkrivaju napetosti između uočene potrebe za primjernim, moralizirajućim knjigama i onima koje bi čitatelju mogle ponuditi razonodu. U radu se pokazuje da među poglavito didaktičnim djelima postoje naznake onoga što će uslijediti. Posvećuje se pozornost jeftinim sveščićima za puk (chapbooks) koje su bile namijenjene djeci, kao i naslovima koji su dosegnuli određeni stupanj opstojnosti.
Bibliografija: str. 22-23.
Summary ; Sažetak.
Keywords: Engleska književnost 19. st. -- Dječja književnost -- Moraliziranje